Testing the Efficacy of Contrast‐Enhanced Ultrasound in Detecting Transplant Rejection Using a Murine Model of Heart Transplantation. Issue 7 (1st February 2017) - Fischer, K.; Ohori, S.; Meral, F. C.; Uehara, M.; Giannini, S.; Ichimura, T.; Smith, R. N.; Jolesz, F. A.; Guleria, I.; Zhang, Y.; White, P. J.; McDannold, N. J.; et al.
Abstract : One of the key unmet needs to improve long‐term outcomes of heart transplantation is to develop accurate, noninvasive, and practical diagnostic tools to detect transplant rejection. Early intragraft inflammation and endothelial cell injuries occur prior to advanced transplant rejection. We developed a novel diagnostic imaging platform to detect early declines in microvascular perfusion (MP) of cardiac transplants using contrast‐enhanced ultrasonography (CEUS). The efficacy of CEUS in detecting transplant rejection was tested in a murine model of heart transplants, a standard preclinical model of solid organ transplant. As compared to the syngeneic groups, a progressive decline in MP was demonstrated in the allografts undergoing acute transplant rejection (40%, 64%, and 92% on days 4, 6, and 8 posttransplantation, respectively) and chronic rejection (33%, 33%, and 92% on days 5, 14, and 30 posttransplantation, respectively). Our perfusion studies showed restoration of MP following antirejection therapy, highlighting its potential to help monitor efficacy of antirejection therapy. Our data suggest that early endothelial cell injury and platelet aggregation contributed to the early MP decline observed in the allografts. High‐resolution MP mapping may allow for noninvasive detection of heart transplant rejection. The data presented have the potential to help in the development of next‐generation imaging approaches to diagnose transplant rejection. Abstract : High‐resolution perfusion mapping using contrast‐enhanced ultrasound detects transplant rejection.